PENGARUH PERMUKAAN ALUR KEMBANG (TREAD PATTERN) BAN TYPE RADIAL PLY TERHADAP ROLLING RESISTANCE - Aditya Krisna Hutomo; Dedy Dwi Laksana; Fx. Kristianta (Jurusan Teknik Mesin Fakultas Teknik Universitas Jember, 2017)
Rolling Resistance is a resistance to the wheels that will and have been rolling due to the force of friction between the wheels with the road surface of the wheel. Rolling resistance is influenced by four factors, that is vehicle weight, road surface, transmission, and tires. This study usefull to determine the influence of tread pattern surface to force and coefficient rolling resistance, tire surface contact area and tire pressure value. In this study using motorcycle tires with size 90/90-17. The tire used is a tire with RIB tread pattern (straight groove) and LUG tread pattern (zig-zag groove). Each type of RIB and LUG tread pattern used each of two tires that is the type of simple tread pattern and the complex tread pattern. From the results of the study showed that the tire with a simple tread pattern will produce a small force of rolling resistance but will result in a larger surface tire surface contact than the tire with the complex tread pattenr. While for the tire with the type complex tread pattern has a greater pressure value that will produce a great rolling resistance force. For tires get the best rolling resistance force is the tire with a simple LUG tread pattern of 10.234 N and followed by a tire with a simple RIB tread pattern type of 10.563 N. Keywords: tread pattern, rolling resistance, rib, lug.